The development of self-educational competence of a contemporary teacher as a theoretical and praxiological problem - Коновал, Олександр Андрійович; Туркот, Тетяна Іванівна (Pedagogy of Higher and Secondary Education, 2015)
Konoval O. A. Turkot T. I. The development of self-educational competence of a contemporary teacher as a theoretical and praxiological problem. The article analyzes the results of the experimental work conducted to find effective means of self-guided students’ work in higher educational institutions. According to the results of conducted analysis the authors substantiate the necessity of researching the problem of professional and pedagogical self-education on the basis of competence approach. The requirements for self- educational competency of contemporary teachers are defined. The reasons of reduced motivation for self-educational competence are clarified. The measures concerning the development of self-educational competence of students and practical teachers in contemporary educational environment are proposed.